Population genomics of the killer whale indicates ecotype evolution in sympatry involving both selection and drift - Andre Moura; John G. Kenny; Roy Chaudhuri; Margaret A. Hughes; Andreanna J. Welch; Ryan R. Reisinger; P. J. Nico de Bruyn; Marilyn E. Dahlheim; Neil Hall; A. Rus Hoelzel (2014)
The evolution of diversity in the marine ecosystem is poorly understood, given the relativelyhigh potential for connectivity, especially for highly mobile species such aswhales and dolphins. The killer whale (Orcinus orca) has a worldwide distribution,and individual social groups travel over a wide geographic range. Even so, regionalpopulations have been shown to be genetically differentiated, including among differentforaging specialists (ecotypes) in sympatry. Given the strong matrifocal socialstructure of this species together with strong resource specializations, understandingthe process of differentiation will require an understanding of the relative importanceof both genetic drift and local adaptation. Here we provide a high-resolution analysisbased on nuclear single-nucleotide polymorphic markers and inference about differentiationat both neutral loci and those potentially under selection. We find that all populationcomparisons, within or among foraging ecotypes, show significantdifferentiation, including populations in parapatry and sympatry. Loci putativelyunder selection show a different pattern of structure compared to neutral loci and areassociated with gene ontology terms reflecting physiologically relevant functions (e.g.related to digestion). The pattern of differentiation for one ecotype in the North Pacificsuggests local adaptation and shows some fixed differences among sympatric ecotypes.We suggest that differential habitat use and resource specializations have promotedsufficient isolation to allow differential evolution at neutral and functional loci, butthat the process is recent and dependent on both selection and drift.